Unpacking History: Diasporic Voices and Visions (Cinéma & Cie. Film and Media Studies Journal, 2017)
This essay investigates the different ways memory is articulated by contemporary writing and artworks that emerge from experiences of migration, exile, diaspora, and cultural hybridity. These productions express a creative resistance connected to narration and participation, while proposing alternative ways of opening the archive from the perspective of the voices and visions that are completely absent or pushed to the margins. For example, the encounters with the histories and the bodies evoked by Derek Walcott, as well as the innovative and trans-local languages proposed by the contemporary visual artists and lmmakers considered in this article, question the limits of historiography, multiculturalism, and institutional practices of archiving through lost traces and inappropriate objects.